Lessons Learned from Sudan Ebola Virus Disease (SUDV) Preparedness in Rwanda: A Comprehensive Review and Way Forward - Rwagasore, Edson; Mucunguzi, Valois H.; Benimana, Jean Luc; Rwagitinywa, Bruce; Muvunyi, Claude Mambo (Journal of Epidemiology and Global Health, 2023)
Ebola Virus Disease (EVD) is a severe and often fatal illness that affects humans and has significant public health implications, including high mortality rates, strain on healthcare systems, and social and economic disruption. On 20 September 2022, Uganda declared an Ebola disease outbreak caused by the Sudan ebolavirus species. The neighboring countries of Uganda were classified by World Health Organization (WHO) as being at high risk of Sudan Ebola Virus Disease (SUDV) importation. The country of Rwanda implemented different sustainable strategies and activities to prepare and ensure a timely and effective response to SUDV outbreaks once it has arrived in the country. We aimed to highlight the sustainable strategies and activities implemented for SUDV preparedness and the subsequent lessons learnt in Rwanda.